How We Count Hunger Matters - Frances Moore Lappe; Jennifer Clapp; Molly Anderson; Robin Broad; Ellen Messer; Thomas Pogge; Timothy Wise (Ethics & International Affairs, 2013)
Hunger continues to be one of humanity's greatest challenges despite the existence of a more-than-adequate global food supply equal to 2,800 kilocalories for every person every day. In measuring progress, policy-makers and concerned citizens across the globe rely on information supplied by the Food and Agriculture Organization (FAO), an agency of the United Nations. In 2010 the FAO reported that in the wake of the 2007–2008 food-price spikes and global economic crisis, the number of people experiencing hunger worldwide since 2005–2007 had increased by 150 million, rising above 1 billion in 2009. However, in its State of Food Insecurity in the World 2012 (SOFI 12) the FAO presented new estimates, having revamped its methods and reinterpreted its hunger data back to 1990. The revised numbers for the period 1990–1992 to 2010–2012 reverse the trend to a steadily falling one. Based on the FAO's new calculations, extreme undernourishment peaked in 1990 at a record-breaking one billion, followed by a significant decline through 2006, when progress stalled but did not reverse (see chart below).